A survey of English teacher's opinions in the Johannesburg area on a language policy for education in a post-apartheid South Africa - Cachalia, Nazira, Vahed (My University, 1993)
The formulation of language policy in South Africa is inextricably bound up with the ideology of Apartheid. The "official" language, English and particularly Afrikaans are associated with race-ru1e and the exercise of state power. Many south Africans, whose mother-tongue is neither are compelled to learn these European languages for economic reasons [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Education University of the Witwatersrand, Johannesburg for the Degree of Master of Education. Johannesburg 1993
Keywords: Language and education -- South Africa; Language policy -- South Africa